Synergistic Impact of The Combination of Moringa Leaves and Butterfly Pea Flowers Infusion on Cognitive Enhancement - Annie Rahmatillah; Anna Fitriawati; Anisa Fadilah Kumala Putri (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Oxidative stress can induce memory loss, which may be mitigated by antioxidants. Moringa leaves (Moringa oleifera) and butterfly pea flowers (Clitoria ternatea) possess flavonoid chemicals that function as natural antioxidants. This study seeks to evaluate the impact of combined Moringa leaf and butterfly pea flower infusions on enhancing the memory of mice and to identify the optimal dosage. The research utilized male white mice (Mus musculus), categorized into six groups: a normal group, a negative control (aquadest), a positive control (Ginkgo biloba), and three treatment groups receiving various infusion doses. The procedure had three phases: acclimatization (T0), intraperitoneal administration of hyoscine butylbromide (T1), and therapy (T2). The manufacture of INDUK BUNTEL (an infusion of moringa leaves and butterfly pea flowers) was conducted using an infusion extraction method. Testing on test subjects was conducted utilizing the Radial Arm Maze methodology. The findings indicated that the infusion combination at dose III (100 mg/KgBW: 100 mg/KgBW) was the most efficacious in enhancing the memory of mice. The mean mistake rate in mice was 16.44%, representing the lowest score among the treatment groups. The one-way ANOVA test indicated no significant difference across treatment groups with three distinct dose combinations (p > 0.05).